UNC79 and UNC80, Putative Auxiliary Subunits of the NARROW ABDOMEN Ion Channel, Are Indispensable for Robust Circadian Locomotor Rhythms in Drosophila. - Lear, B.C.; Darrah, E.J.; Aldrich, B.T.; Gebre, S.; Scott, R.L.; Nash, H.A.; Allada, R. (PLoS ONE, 2013)
In the fruit fly Drosophila melanogaster, a network of circadian pacemaker neurons drives daily rhythms in rest and activity. The ion channel NARROW ABDOMEN (NA), orthologous to the mammalian sodium leak channel NALCN, functions downstream of the molecular circadian clock in pacemaker neurons to promote behavioral rhythmicity. To better understand the function and regulation of the NA channel, we have characterized two putative auxiliary channel subunits in Drosophila, unc79 (aka dunc79) and unc80 (aka CG18437). We have generated novel unc79 and unc80 mutations that represent strong or complete loss-of-function alleles. These mutants display severe defects in circadian locomotor rhythmicity that are indistinguishable from na mutant phenotypes. Tissue-specific RNA interference and rescue analyses indicate that UNC79 and UNC80 likely function within pacemaker neurons, with similar anatomical requirements to NA. We observe an interdependent, post-transcriptional regulatory relationship among the three gene products, as loss of na, unc79, or unc80 gene function leads to decreased expression of all three proteins, with minimal effect on transcript levels. Yet despite this relationship, we find that the requirement for unc79 and unc80 in circadian rhythmicity cannot be bypassed by increasing NA protein expression, nor can these putative auxiliary subunits substitute for each other. These data indicate functional requirements for UNC79 and UNC80 beyond promoting channel subunit expression. Immunoprecipitation experiments also confirm that UNC79 and UNC80 form a complex with NA in the Drosophila brain. Taken together, these data suggest that Drosophila NA, UNC79, and UNC80 function together in circadian clock neurons to promote rhythmic behavior.